Interactions of Gender and Number Agreement: Evidence from Bosnian/Croatian/Serbian. (15th June 2018) - Puškar, Zorica
Abstract: Split hybrid nouns in Bosnian/Croatian/Serbian display two sets of interesting properties: they can bear both natural and grammatical gender, and which gender participates in agreement depends on the number of the noun. While in the singular they invariably trigger natural‐gender (masculine) agreement, optionality between natural‐ and grammatical‐gender (feminine) agreement obtains in the plural. Such nouns pose two theoretical challenges: (i) Agree must be able to operate on two kinds of gender, and (ii) gender must be allowed to interact with number. Previous accounts propose complex mapping between semantic, syntactic, and class features but ultimately cannot derive the obligatoriness of natural‐gender agreement in the singular and natural–grammatical optionality in the plural in a unified way. I provide a Minimalist analysis of hybrid nouns' agreement, combining the formal tools of feature hierarchies and relativized probing, which derive the obligatoriness of natural gender in the singular, with Cyclic Agree with different orders of Agree operations, which derives the natural–grammatical optionality as intervention effects.